Multilayered tissue mimicking skin and vessel phantoms with tunable mechanical, optical, and acoustic properties. Issue 6 (30th November 2016) - Chen, Alvin I.; Balter, Max L.; Chen, Melanie I.; Gross, Daniel; Alam, Sheikh K.; Maguire, Timothy J.; Yarmush, Martin L.
Abstract : Purpose: This paper describes the design, fabrication, and characterization of multilayered tissue mimicking skin and vessel phantoms with tunable mechanical, optical, and acoustic properties. The phantoms comprise epidermis, dermis, and hypodermis skin layers, blood vessels, and blood mimicking fluid. Each tissue component may be individually tailored to a range of physiological and demographic conditions. Methods: The skin layers were constructed from varying concentrations of gelatin and agar. Synthetic melanin, India ink, absorbing dyes, and Intralipid were added to provide optical absorption and scattering in the skin layers. Bovine serum albumin was used to increase acoustic attenuation, and 40 μ m diameter silica microspheres were used to induce acoustic backscatter. Phantom vessels consisting of thin‐walled polydimethylsiloxane tubing were embedded at depths of 2–6 mm beneath the skin, and blood mimicking fluid was passed through the vessels. The phantoms were characterized through uniaxial compression and tension experiments, rheological frequency sweep studies, diffuse reflectance spectroscopy, and ultrasonic pulse‐echo measurements. Results were then compared to in vivo and ex vivo literature data. Results: The elastic and dynamic shear behavior of the phantom skin layers and vessel wall closely approximated the behavior of porcine skin tissues and human vessels. Similarly, the optical properties of the phantom tissue components in the wavelength range of 400–1100 nm, as well as the acoustic properties in the frequency range of 2–9 MHz, were comparable to human tissue data. Normalized root mean square percent errors between the phantom results and the literature reference values ranged from 1.06% to 9.82%, which for many measurements were less than the sample variability. Finally, the mechanical and imaging characteristics of the phantoms were found to remain stable after 30 days of storage at 21 °C. Conclusions: The phantoms described in this work simulate the mechanical, optical, and acoustic properties of human skin tissues, vessel tissue, and blood. In this way, the phantoms are uniquely suited to serve as test models for multimodal imaging techniques and image‐guided interventions.